Carrion and scientific positivism - Pesce, Hugo (1957)
Order Speech delivered by Dr. Hugo Pesce in the Tribute of the Faculty of Medicine at DANIEL A. CARRION in the centenary of his birth, in Lima on August 8, 1957.